Integration Consumer Response during the Pandemic Covid-19 on Advertising: Perception Study on Eco Labeling and Eco Brand Products Eco Care - Rennyta Yusiana; Arry Widodo; Umi Sumarsih (Inclusive Society and Sustainability Studies, 2021)
Environmentally friendly assurance, or commonly known as eco label, indicates that the product is guaranteed quality. Currently, the Indonesian government supports green marketing actions carried out by companies. One of the supports provided by the government is the provision of eco labels for green products. To analyze an advertisement through the concept of green marketing, one of the supporting elements of communication in promotion is and eco brand and eco label. This research is a descriptive analysis using quantitative methods involving 100 respondents determined by the Bernoulli formula. Respondents are consumers who use eco care products during the covid-19 pandemic. The measurement scale used in this study is the ordinal scale and the Likert scale. This research used multiple linear regression analysis. The results of hypothesis testing demonstrate a significant difference in customer buying behavior between the eco label, eco brand and environmental advertisement. The partial hypothesis test (t test) revealed that the factors (e.g eco label, eco brand and environmental advertisement) had a substantial impact on customer buying behavior. The coefficient of determination describes the relationship between these variables. Time affects most of consumer buying behavior and the rest is influenced by external factors. This study focusing the determine the effect of using environmentally friendly products on consumers to buy as measured through, eco brands, environmental advertisements and eco labels in Bandung-Indonesia either directly or indirectly. Furthermore, analysis is deemed necessary to expand the sample size and investigate a broader cluster of samples to boost the understanding of consumer purchase behavior. This study provides input on relevant theories on the theory of reasoned action, especially on the sub-variables regarding the eco label, eco brand, environmental advertisement, and consumer purchase behavior, and supports increased use and consumer behavior.